Industrialisation and society : a social history, 1830-1951 - Hopkins, Eric (Routledge, 2000)
An essential introduction to the effects of industrialisation on British society, from Queen Victoria's reign to the birth of the Welfare State in the 1940s. It includes sections on the Victorian inheritance and the two world wars.